2011
DOI: 10.1002/ima.20281
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the nonstationary neural activity in motor cortex for brain machine interfaces

Abstract: Previous decoding algorithms used in brain machine interfaces (BMIs) usually seek a static functional mapping between the spatio-temporal neural activity and behavior and assume that the neural spike statistics do not change over time. However, recent work indicates the significant variance in neural activities, which suggests the nonfeasibility of the stationary assumptions on the neural signal sequences. To track the time-changing neural activity during the nonlinear decoding process, we developed a time-var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The variation in preferred directions and the number of tuning directional signals shown in figure 5(b) in our study further confirmed the variability of neural encoding under the effect of nonstationarity of neural activities. Previous studies showed the non-stationarity could deteriorate the decoding performance of spike signals in static decoder over time even in several hours during the same session where no degradation of neural recording was observed [33,34]. Recently, Flint's study also found significantly reduced accuracy in offline decoding of LFPs for almost all sessions after day 0 compared to the accuracy on day 0, while the recording quality of neural signals did not obviously decay [22].…”
Section: The Effect Of Non-stationarity Of Neural Activities On Long-...mentioning
confidence: 97%
See 2 more Smart Citations
“…The variation in preferred directions and the number of tuning directional signals shown in figure 5(b) in our study further confirmed the variability of neural encoding under the effect of nonstationarity of neural activities. Previous studies showed the non-stationarity could deteriorate the decoding performance of spike signals in static decoder over time even in several hours during the same session where no degradation of neural recording was observed [33,34]. Recently, Flint's study also found significantly reduced accuracy in offline decoding of LFPs for almost all sessions after day 0 compared to the accuracy on day 0, while the recording quality of neural signals did not obviously decay [22].…”
Section: The Effect Of Non-stationarity Of Neural Activities On Long-...mentioning
confidence: 97%
“…To reduce the effect of non-stationarity on long-term decoding stability, adaptive decoders have been used which could track the variable mapping between neural activities and kinematics. Several studies have proved that the offline decoding performance could be significantly improved by using adaptive decoders [33][34][35]. Therefore, it is a good way to solve the issues about the effect of non-stationarity on neural decoding stability.…”
Section: The Effect Of Non-stationarity Of Neural Activities On Long-...mentioning
confidence: 99%
See 1 more Smart Citation
“…One way to cope with the variability of neural activity is to use nonparametric kernel regression approaches [23][24][25][26]. Instead of learning a specific function, kernel regression approaches do not assume function forms and only assume that signals with similar inputs should share similar outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Given incoming neural signals, they find the neighborhood of the neural data in the training set and compute the locally weighted average of the corresponding kinematics as the output [23]. In this way, kernel regression approaches can fit diverse relationships between neural signals and kinematics flexibly in subsets of data to model neural pattern changes; thus, more accurate and robust BMI performance can be achieved [24][25][26]. However, directly extending kernel regression approaches to neural decoding problems can be suboptimal.…”
Section: Introductionmentioning
confidence: 99%